Development of instrumentation for measurements of two components of velocity with a single sensing element. (18th January 2018) - Byers, C P; Fu, M K; Fan, Y; Hultmark, M
Abstract: A novel method of obtaining two orthogonal velocity components with high spatial and temporal resolution is investigated. Both components are obtained utilizing a single sensing nanoribbon by combining the two independent operating modes of classic hot wire anemometry and the newly discovered elastic filament velocimetry (EFV). In contrast to hot wire anemometry, EFV measures fluid velocity through correlating the fluid forcing with the internal strain of the wire. In order to utilize both modes of operation, a system that switches between the two operating modes is built and characterized, and the theoretically predicted sensing response time in water is compared to experimental results. The sensing system is capable of switching between the two modes of operation at a frequency of 100 kHz with minimal attenuation with an uncompensated repetition rate up to 3 kHz or up to 10 kHz utilizing modest signal compensation. While further characterization of the sensor performance in air is needed, this methodology enables a technique for obtaining well-resolved yet cost-efficient directional measurements of flow velocities which, for example, can be used for distributed measurements of velocity or measurements of turbulent stresses with excellent spatial resolution.